Human Capital in Green Economies: A Systematic Review of Workforce Transformation of Environmental Sustainability - Nofriansyah, Nofriansyah; Dahlan, Dadang; Sutarni, Nani; Rahayu, Sri; Wardiman, Jery; Supriatna, Endang; Melia, Maya (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
The relevance of development that is focused on both environmental sustainability and economic improvement is shown by the current global economic boom. With an emphasis on green skills development, green human resource management (GHRM), and its effects on environmental sustainability, this article provides a thorough overview of the role that human capital plays in assisting workforce transformation towards a green economy. This study examined 20 pertinent articles out of 1,760 that were found in the Semantic Scholar and Scopus databases using the PRISMA approach. The findings demonstrate that the adoption of green technology, particularly in the fields of sustainable industry and renewable energy, depends on the development of green human capital. To speed up the development of green talents, cooperation between the government, business community, and academic institutions is also required. The study also identifies significant prospects for job creation and environmental impact reduction, as well as obstacles to the green economy's implementation, such as structural impediments and skills gaps. The article's conclusion is that significant investments in education and training, along with policies that promote sustainability and worker well-being, are necessary to shift the workforce toward a green economy.